2005
DOI: 10.2528/pier04052002
|View full text |Cite
|
Sign up to set email alerts
|

Elliptical and Circular Step-Index Fibers With Conducting Helical Windings on the Core-Cladding Boundaries for Different Winding Pitch Angles - A Comparative Modal Dispersion Analysis

Abstract: Abstract-The propagation characteristics of an elliptical step-index fiber with a conducting helical winding on the core-cladding boundary are investigated analytically and compared with those of a circular step index fiber with a conducting radial winding. Our optical waveguides are unconventional: in view of the existence of helical conducting windings on the core-cladding boundaries. Appropriate coordinate systems, circular cylindrical and elliptic cylindrical, are chosen for the circular and elliptical fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Watkins himself cited the works of Brillouin [26], Kornhauser [27], Mathers and Kino [28]. Kumar and Singh [29][30][31] have also presented earlier the study of elliptical fibers with conducting helical windings, and it was reported that the effect of the helical pitch angle was almost negligible for the guides having small eccentricity values. Further, in that work the parameter related to the helical pitch angle was not present in all terms of the dispersion relation.…”
Section: Introductionmentioning
confidence: 98%
“…Watkins himself cited the works of Brillouin [26], Kornhauser [27], Mathers and Kino [28]. Kumar and Singh [29][30][31] have also presented earlier the study of elliptical fibers with conducting helical windings, and it was reported that the effect of the helical pitch angle was almost negligible for the guides having small eccentricity values. Further, in that work the parameter related to the helical pitch angle was not present in all terms of the dispersion relation.…”
Section: Introductionmentioning
confidence: 98%
“…Fast-wave analysis of an inhomogeneously-loaded helix enclosed in a cylindrical waveguide has been published by Ghosh et al [12]. The characteristics of the propagation of an elliptical step-index fiber with a conducting helical winding on the core-cladding boundary are investigated analytically [13]. The core and the cladding regions are assumed to have constant real refractive indices n 1 and n 2 , where…”
Section: Introductionmentioning
confidence: 99%
“…The tape-helix model has been used which takes into account the effect of the space-harmonics, and is used particularly in the cases that the structure is operated at high voltages and for high helix pitch angles. The propagation characteristics of an elliptical step-index fiber with a conducting helical winding on the core-cladding boundary [12] are investigated analytically where the coordinate systems are chosen for the circular and elliptical fibers. In their waveguides the core and the cladding regions are assumed to have constant real refractive indices n 1 and n 2 , where n 1 > n 2 .…”
Section: Introductionmentioning
confidence: 99%